Dopamine Modulates Delta-Gamma Phase-Amplitude Coupling in the Prefrontal Cortex of Behaving Rats - Andino-Pavlovsky, Victoria; Souza, Annie C.; Scheffer-Teixeira, Robson; Tort, Adriano B. L.; Etchenique, Roberto; Ribeiro, Sidarta (Frontiers in Neural Circuits, 2017)
Dopamine release and phase-amplitude cross-frequency coupling (CFC) have independently been implicated in prefrontal cortex functioning. To causally investigate whether dopamine release affects phase-amplitude comodulation between different frequencies in local field potentials (LFP) recorded from the medial prefrontal cortex (mPFC) of behaving rats, we used RuBiDopa, a light-sensitive caged compound that releases the neurotransmitter dopamine when irradiated with visible light. LFP power did not change in any frequency band after the application of light-uncaged dopamine, but significantly strengthened phase-amplitude comodulation between delta and gamma oscillations. Saline did not exert significant changes, while injections of dopamine and RuBiDopa produced a slow increase in comodulation for several minutes after the injection. The results show that dopamine release in the medial PFC shifts phase-amplitude comodulation from theta-gamma to delta-gamma. The results, albeit preliminary due to the low number of animals studied (N=3), suggest that the dopamine-mediated modification of the frequencies involved in the comodulation may be a mechanism by which this neurotransmitter regulates mPFC functioning.